Application of multiple criteria decision making in the selection of digital forensics software - Stanivuković, Dejan R.; Ranđelović, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Nowadays there is almost no criminal offense in the investigation of which digital evidence does not play a key role. Constant increase of the capacity of media that store digital data leads to  continuous increase of the time necessary to identify and copy (acquire) digital evidence. Selection of appropriate digital forensics software is gaining in importance. Selection of adequate software includes a previous comparative analysis of two or more digital forensics software tools and an optimization process. The objective of the comparative analysis of these software tools is to determine and compare each of their realistic and comparable performances. Optimization aims to determine which of digital forensics software tools has better performances. This paper shows one of possible variants of selecting digital forensics software, using the latest scientific achievements in support of decision making based on the analytic hierarchy process (AHP) method and the Expert Choice computer program.
Keywords: forensics software; digital forensics; expert choice; optimization; digital evidence; comparative analysis